Fіscal policy as an instrument of state national security provision - Klimova , Svitlana; Halynska , Karina; Myrna , Nadiya; Komuniar , Dmytro (Pressing Problems of Public Administration, 2024)
The article highlights the obstacles to combining budgetary and tax policy in Ukraine in the context of hostilities. The ways of ensuring national security are outlined. One of them is fiscal policy, which allows governments not only to counteract economic downturns, reduce unemployment, and ensure price stability, but also to counteract internal and external threats. The purpose of this study is to analyse Ukraine’s fiscal policy under martial law, to formulate problematic issues in the implementation of this policy, and to identify ways to improve the mechanism of developing and implementing this policy in the post-war period in order to strengthen national security During the period of martial law, fiscal policy has taken on new characteristics and new tasks. The time has come to plan the reconstruction of Ukraine and to incorporate into the strategies not only the strengthening of security, law and order, the improvement of the efficiency of public financial management, and the increase of budget revenues, but also new fiscal policy priorities. The sequence of reforms and their timing are important, and improving the efficiency of the use of existing public funds should be implemented in accordance with European principles and standards. Based on the above, we can identify the most problematic issues of state regulation of financial flows in the current environment, i.e. the implementation of the state’s fiscal policy. The first is the relevance of taxes to the needs of both the state and economic entities. The second is to determine the scope of further use of artificial intelligence in the field of public finance and to assign responsibility for the performance of artificial intelligence to a specific public administration body. The third is the low level of efficiency, transparency, and public accountability of public administration bodies responsible for tax control and public finance management. The fourth is the low ability of law enforcement agencies to deter economic crimes due to complicated and time-consuming procedures and weak ties with international organisations. The fifth is the ineffectiveness of regulatory mechanisms, inconsistent legal regulation of relations in the tax sphere in the face of a significant budget deficit. The sixth is the uncertainty of the mechanism for establishing assets and financial liabilities in the temporarily occupied territories of Ukraine. The seventh is the lack of clear criteria for assessing the effectiveness of the state’s fiscal policy.